The Effect of Medical Mask Usage during Physical Activities on Vital Signs, Muscular Endurance, and Physical Fitness Index - Stella Tinia Hasianna; July Ivone; Yohana Christanti; Evelyn Calista (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2022)
The COVID-19 pandemic requires everyone to wear a mask as a preventive measure, including performing physical activities. This study aimed to determine the effect of medical mask use when performing physical exercises on oxygen saturation, vital signs, muscle endurance, and physical fitness index. The experimental analytical quantitative approach, with pre-test and post-test design, was used. Vital signs and oxygen saturation were measured briefly after brisk walking. The Push-up Test was conducted to measure muscle endurance, while the Harvard Step-up Test was used to measure Physical Fitness Index. The procedures were repeated twice, using medical masks and not using medical masks. The research subjects were 28 males aged 17-21 years with normal BMI. The results showed significant differences in the value of systolic blood pressure, pulse, respiratory rate, body temperature, oxygen saturation, muscle endurance, and physical fitness between the exercise using medical masks and not using medical masks. The p-values were 0.000 on all of these variables. A significant difference was also found in diastolic blood pressure with a p-value of 0.001. This study concludes that using medical masks during physical activity increases all vital sign parameters and decreases oxygen saturation, muscle endurance, and physical fitness levels.